2004
DOI: 10.7863/jum.2004.23.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Normal Diaphragmatic Motion and the Effects of Body Composition

Abstract: Objective.To evaluate the quantitative measurement of diaphragmatic motion in healthy subjects and to investigate the effects of different variables such as body mass index and waist circumference on the diaphragmatic motion. Methods. The study included 164 healthy subjects. The subjects were grouped according to age, sex, body mass index, and waist circumference. Measurements of diaphragmatic motion were made by a 3.5-MHz sonographic unit in the M-mode of the system. The posterior diaphragm on both sides was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 19 publications
6
66
0
7
Order By: Relevance
“…Kantarci et al 99 described a mean left diaphragm excursion of 49 Ϯ 11 mm in healthy subjects, which was significantly lower in female, young, and underweight subjects. In a prospective study designed to determine the reference values for diaphragm amplitudes recorded by M-mode ultrasonography, Boussuges et al 84 defined the normal values during tidal and deep breathing in male and female healthy subjects (1.8 Ϯ 0.3 and 7 Ϯ 0.6 cm and 1.6 Ϯ 0.3 and 5.7 Ϯ 1 cm, respectively).…”
Section: Diaphragm Displacementmentioning
confidence: 99%
“…Kantarci et al 99 described a mean left diaphragm excursion of 49 Ϯ 11 mm in healthy subjects, which was significantly lower in female, young, and underweight subjects. In a prospective study designed to determine the reference values for diaphragm amplitudes recorded by M-mode ultrasonography, Boussuges et al 84 defined the normal values during tidal and deep breathing in male and female healthy subjects (1.8 Ϯ 0.3 and 7 Ϯ 0.6 cm and 1.6 Ϯ 0.3 and 5.7 Ϯ 1 cm, respectively).…”
Section: Diaphragm Displacementmentioning
confidence: 99%
“…Some authors have reported that women show 11-20% less diaphragmatic excursion during deep breathing, in comparison with men. (28,29) In the present study, the women showed 5% and 8% less diaphragmatic mobility during ISFOD and ISVOD, respectively, than did the men. Considering that during incentive spirometry, there are maximal amplitude inspiratory patterns, our results are in agreement with those of the studies mentioned above, although the difference was of lesser magnitude in our study.…”
Section: Discussionmentioning
confidence: 73%
“…(30) Our results showed that the mobility/FVC (mm/L) ratio was significantly greater in women than in men, indicating that women performed better than did men on all three types of breathing exercises. One group of authors (28) reported that BMI can be considered another factor affecting diaphragmatic mobility in healthy subjects. In the present study, this variable seems to have had no influence on the results of the comparison between men and women, since the two were similar in terms of BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers assessing diaphragmatic motion using m-mode USI have found that gender, body mass index, waist circumference, and age influence the amount of excursion. 68 These findings highlight the need to further assess the effects of these variables on measurement of muscular function when using m-mode for RUSI.…”
Section: M-mode Ultrasound Imagingmentioning
confidence: 99%